2012
DOI: 10.1111/j.1530-0277.2012.01880.x
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Magnetic Resonance Imaging Study of Spatial Working Memory in Children with Prenatal Alcohol Exposure: Contribution of Familial History of Alcohol Use Disorders

Abstract: Background Heavy prenatal alcohol exposure leads to widespread cognitive deficits, including problems with spatial working memory (SWM). Neuroimaging studies report structural and functional abnormalities in FASD, but interpretations may be complicated by the co-occurrence of a family history of alcoholism. Since, this history is also linked to cognitive deficits and brain abnormalities, it is difficult to determine the extent to which deficits are unique to prenatal alcohol exposure. Methods Age-matched sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 53 publications
(69 reference statements)
0
37
0
1
Order By: Relevance
“…Less efficient task related networks or compensation for other less active regions have been suggested as an explanation to increased activation in alcohol-exposed children. 175,190 Similar compensatory mechanisms could possibly explain our finding of increased prefrontal activation in the opioid-exposed group. On the other hand, several studies have reported working memory deficits with corresponding lower brain activation including prefrontal areas in groups of children with prenatal exposure to alcohol and methamphetamine.…”
Section: Paper IIImentioning
confidence: 63%
See 1 more Smart Citation
“…Less efficient task related networks or compensation for other less active regions have been suggested as an explanation to increased activation in alcohol-exposed children. 175,190 Similar compensatory mechanisms could possibly explain our finding of increased prefrontal activation in the opioid-exposed group. On the other hand, several studies have reported working memory deficits with corresponding lower brain activation including prefrontal areas in groups of children with prenatal exposure to alcohol and methamphetamine.…”
Section: Paper IIImentioning
confidence: 63%
“…145,175,189,190 In these studies varying degrees of behavioral differences between alcohol-exposed children and unexposed controls have been found. Less efficient task related networks or compensation for other less active regions have been suggested as an explanation to increased activation in alcohol-exposed children.…”
Section: Paper IIImentioning
confidence: 98%
“…In addition to examining differences in task-activated patterns between alcoholics and controls, fMRI paradigms have been useful in detecting group differences related to preexisting conditions in and predisposing genetic factors to alcoholism occurring in alcoholism (e.g., Cardenas et al, 2005;Claus, Ewing, Filbey, Sabbineni, & Hutchison, 2011;Cservenka & Nagel, 2012;Hill, Terwilliger, & McDermott, 2012;Jamadar et al, 2012;Kareken et al, 2010;Norman et al, 2013;Schuckit et al, 2011;Silveri, Rogowska, McCaffrey, & Yurgelun-Todd, 2011;Villafuerte et al, 2012;Weiland et al, 2013;Wetherill et al, 2012). Regarding responsivity to alcohol cues (Schacht, Anton, & Myrick, 2013;Squeglia, Jacobus, & Tapert, 2014), one fMRI study used a passive viewing paradigm of positive, negative, or neutral words to examine high (vulnerable)-and low (resilient)-drinking late adolescents of alcoholic parents (Heitzeg, Nigg, Yau, Zubieta, & Zucker, 2008).…”
Section: Frontostriatal Circuitrymentioning
confidence: 99%
“…The impact of prenatal alcohol exposure can be dissociated from other potential explanatory variables. When examined in relation to family history of alcohol use disorders, prenatal alcohol exposure independently predicted increased activation in left middle and superior frontal brain regions [137]. In a direct comparison of adolescents with prenatal alcohol exposure or ADHD, behavioral profiles were similar but the two groups showed differences in how cortical brain regions were recruited for spatial working memory [138].…”
Section: Working Memorymentioning
confidence: 99%